Surface Immunoproteomics Reveals Potential Biomarkers in Alicyclobacillus acidoterrestris - Shi, Yiheng; Yue, Tianli; Zhang, Yipei; Wei, Jianping; Yuan, Yahong (Frontiers in Microbiology, 2018)
Alicyclobacillus acidoterrestris is a major putrefying bacterium that can cause pecuniary losses in the global juice industry. Current detection approaches are time-consuming and exhibit reduced specificity and sensitivity. In this study, an immunoproteomic approach was utilized to identify specific biomarkers from A. acidoterrestris for the development of new detection methods. Cell surface-associated proteins were extracted and separated by 2-D (two-dimensional) gel electrophoresis. Immunogenic proteins were detected by Western blot analysis using antisera against A. acidoterrestris. Twenty-two protein spots exhibiting immunogenicity were excised and eighteen of the associated spots were successfully identified by matrix-assisted laser desorption/ionization time-of-flight tandem mass spectrometry (MALDI-TOF/TOF MS). These proteins were observed to be involved in energy and carbohydrate metabolism, transmembrane transport, response to oxidative stress, polypeptide biosynthesis, and molecule binding activity. This is the first report detailing the identification of cell surface-associated antigens of A. acidoterrestris. The identified immunogenic proteins could serve as potential targets for the development of novel detection methods.